2018
DOI: 10.1248/bpb.b18-00002
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Effects of Formononetin and Temozolomide on Glioma C6 Cells

Abstract: Temozolomide (TMZ) is currently the first-line drug used for clinical postoperative or non-surgical chemotherapy for glioma, but acquired and intrinsic resistance to TMZ limits its application. The anti-proliferative effect of formononetin on human glioma cells had been confirmed. To improve therapeutic effects of TMZ, we studied the effect of formononetin in combination with TMZ on C6 glioma cells. The anti-proliferative effect of C6 cells was tested by 3-4,5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Our results demonstrated that intrinsic or mitochondrial pathway is involved in the induction of apoptosis after TMZ treatment in RH30 cells (significant increase in caspase-9 activation) while TMZ-induced apoptosis is not caspase-9 dependent in C2C12 cells. It has been reported that TMZ-induced apoptosis is caspase dependent in different models, including glioma cells 68 70 , and human glioma stem cells 71 . It has been previously reported that TMZ induces endoplasmic reticulum (ER)-stress with subsequent unfolded protein response in many cell models.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that intrinsic or mitochondrial pathway is involved in the induction of apoptosis after TMZ treatment in RH30 cells (significant increase in caspase-9 activation) while TMZ-induced apoptosis is not caspase-9 dependent in C2C12 cells. It has been reported that TMZ-induced apoptosis is caspase dependent in different models, including glioma cells 68 70 , and human glioma stem cells 71 . It has been previously reported that TMZ induces endoplasmic reticulum (ER)-stress with subsequent unfolded protein response in many cell models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, formononetin also worked synergistically with temozolomide against glioma C6 cells. The combination of formononetin with temozolomide enhanced apoptosis and inhibited migration of glioma cells (Zhang et al, 2018b).…”
Section: Combinatorial Use Of Formononetin With Other Chemotherapeutimentioning
confidence: 99%
“…Isoflavones, like formononetin, has increased benefits with fewer side effects when used as a combination drug with chemotherapy or as a postoperative adjuvant therapy 46 , 47 . We also found that MEQ displayed few adverse effects in mice, suggesting that MEQ may have clinical applications in combination with other chemotherapeutic drugs in TNBC treatment.…”
Section: Discussionmentioning
confidence: 99%